2006
DOI: 10.1111/j.1440-1746.2006.04298.x
|View full text |Cite
|
Sign up to set email alerts
|

Intrafamilial prevalence of hepatitis B virus in Western Brazilian Amazon region: Epidemiologic and biomolecular study

Abstract: Intrafamilial transmission of HBV is evident in the present study and is possibly associated with the presence of more than one HBV carrier in the family and the shared use of toothbrushes among household contacts. Genotype analysis confirms intrafamilial transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
51
0
13

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 17 publications
3
51
0
13
Order By: Relevance
“…Studies carried out in the Amazon region suggest that HBV transmission is associated with living with an HBV carrier and with sharing items of personal use. 6,7 We observed a high prevalence rate of total anti-HDV in these three areas. Notably, similar rates were reported in the Amazon region 26,52,53 suggesting that HDV has not yet disappeared from HBV hyperendemic areas.…”
mentioning
confidence: 78%
See 2 more Smart Citations
“…Studies carried out in the Amazon region suggest that HBV transmission is associated with living with an HBV carrier and with sharing items of personal use. 6,7 We observed a high prevalence rate of total anti-HDV in these three areas. Notably, similar rates were reported in the Amazon region 26,52,53 suggesting that HDV has not yet disappeared from HBV hyperendemic areas.…”
mentioning
confidence: 78%
“…Vertical transmission does not appear to be significant, but intra-family transmission, associated with the presence of an HBV carrier is commonly described. 6,7 The HBV is classified into 10 genotypes (A to J), originally distributed within specific populations. Human migrations and miscegenation defined the pattern of geographical distribution observed today.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Brazil, the presence of genotype G has been rarely seen (Lobato et al 2006, Mendes-Correa et al 2008. Bottecchia et al (2008) identified genotype G in a patient infected with HBV only and in two patients co-infected with HIV.…”
Section: Discussionmentioning
confidence: 99%
“…In this same area, Lobato et al (2006) showed intrafamilial transmission to be the most important route of HBV dissemination in Acre. Once more, the high prevalence of genotype A and F was reported [10].…”
Section: Epidemiological Datamentioning
confidence: 99%